2018
DOI: 10.1111/odi.12927
|View full text |Cite
|
Sign up to set email alerts
|

Salivary fetuin‐A, S100A12, and high‐sensitivity C‐reactive protein levels in periodontal diseases

Abstract: Salivary fetuin-A and S100A12 levels decreased with increasing severity of periodontal disease. These results suggest that salivary fetuin-A may play an important role as a negative acute-phase protein in periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
1
8
0
2
Order By: Relevance
“…In logistic regression analysis, advanced periodontitis was significantly associated with a low fetuin-A level (OR 1.66) and male sex (OR 2.03). Salivary fetuin-A levels were higher after periodontal treatment than at baseline in a previous study [24]. Future studies should thus examine whether serum or salivary fetuin-A level is a potential biomarker of peri- odontitis.…”
Section: Discussionmentioning
confidence: 73%
“…In logistic regression analysis, advanced periodontitis was significantly associated with a low fetuin-A level (OR 1.66) and male sex (OR 2.03). Salivary fetuin-A levels were higher after periodontal treatment than at baseline in a previous study [24]. Future studies should thus examine whether serum or salivary fetuin-A level is a potential biomarker of peri- odontitis.…”
Section: Discussionmentioning
confidence: 73%
“…However, few studies are reporting the role of salivary AHSG in diseases like periodontal disease, obstructive sleep apnea etc. 42,43 . We report here for the first time, upregulated salivary AHSG levels in oral cancer (in comparison to healthy controls).…”
Section: Discussionmentioning
confidence: 99%
“…This association is in accordance several other studies indicating reduced levels of Fetuin A with inflammatory cytokines. 24,33,34,35 Also, previous in vitro study by Schure et al has shown that complete digestion of human Fetuin occurs within 12 hours when it is incubated with a 10fold molar excess of MMP-7. 17 Therefore, MMP-7 is considered to be relevant for the study of pathophysiological degradation of Fetuin A.…”
Section: Figure 2 Comparison Of Serum Fetuin a And Mmp-7 Levels Betwmentioning
confidence: 98%